Migration - Karski, Karol (International Law From A Central European Perspective, 2022)
Migration is inherent in human history. It is what we name a change of habitual residence or temporary residence by natural persons. It can be permanent or temporary. Its purpose may be, inter alia, tourism, education, treatment, pilgrimage, or earning money. Of course, also in this case we encounter a number of definitions that define a narrower or broader concept of migration. These forms include emigration, immigration, re-emigration, refugeehood, evacuation, and repatriation. The issue of admitting foreigners to a territory is, as a rule, regulated by national law. The freedom of action of states is, however, to some extent limited by international agreements. International law pays particular attention to refugees. This matter is regulated, in particular, by the Geneva Convention relating to the Status of Refugees of 1951, amended by the New York Protocol of 1967. These issues are also tackled in the acts of international humanitarian law, including the Fourth Geneva Convention relative to the protection of civilian persons in time of war of 1949 and the First Additional Protocol of 1977 to the Geneva Conventions of 1949. Respective legal acts have been also adopted by the European Union and include Directive 2011/95/EU of the European Parliament and of the Council on standards for the qualification of third-country nationals or stateless persons as beneficiaries of international protection, for a uniform status for refugees or for persons eligible for subsidiary protection, and for the content of the protection granted and Regulation (EU) No 604/2013 of the European Parliament and of the Council establishing the criteria and mechanisms for determining the Member State responsible for examining an application for international protection lodged in one of the Member States by a third-country national or a stateless person. Migrant workers are another form of migrants, whose status is regulated by the conventions of the International Labour Organization and International Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families of 1990. In Europe—within the scope of the Council of Europe—this issue is regulated by the European Convention on the Legal Status of Migrant Workers of 1977. Other acts of international law, including universal treaties such as International Covenant on Civil and Political Rights of 1966, UN Convention against Torture and Other Cruel, Inhuman or Degrading Treatment or Punishment of 1984, and UN Convention on the Rights of the Child of 1989 refer partly to some aspects of the status of foreigners. Regional acts such as the Charter of Fundamental Rights of the European Union and the European Convention on Human Rights also refer to these issues. The international community has established a number of institutions handling the status and rights of migrants as a whole and their individual types. These institutions include the UN High Commissioner for Refugees and the UN Special Rapporteur on the Human Rights of Migrants and the Committee on the Protection of the Rights of All Migrant Workers and Members of Their Families, which is a treaty body of the International Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families. KEYWORDS: migrants, refugees, states, treaties